Osmoregulation Pattern of Fingerling Vanname Shrimp (Litopenaeus vannamei) Rearing in Three Molt Stage Iso-Osmotic Media - Sutrisno Anggoro; Djoko Suprapto; Frida Purwanti (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2018)
Vanname shrimp (Litopenaeus vannamei) is one of euryhaline Crustacean that able to adapt to a wider range of salinities. The need of suitable media for a given size and molting stage of shrimp is a key factor of the success of shrimp culture. In order to ensure the success of fingerling Vanname shrimp (FVS) rearing, it is indispensable to provide suitable osmotic media for the molting process. This research was aimed to examine and determine isoosmotic media that complies with physiological process of FVS. The research was done in laboratory scale with Completely Randomized Design. FVS was acclimated to three salinities level i.e. 15-16 ‰ as the postmolt isosmotic media, 25-26 ‰ as the intermolt isosmotic media, and 29-30 ‰ as the premolt and molt isosmotic media with three replications. The result showed that in the media of 25-26 ‰, the osmotic work revealed the minimal level and it enhanced the growth rate without changing the amino acids composition in the shrimp body tissue.